TPACK Based Open Ended Approach to Improve Mathematical Reasoning Skills - Khori Adelina Fitriani (Universitas Sebelas Maret, 2020)
Elementary school mathematics learning in Indonesia can be said to be still lacking. During this time, students tend to dislike or even fear mathematics subjects, especially in the context of mathematical reasoning. In the field of education, teachers must be able to develop students' mathematical reasoning by using appropriate strategies. So we need appropriate approaches and media to develop mathematical reasoning abilities. The purpose of this study to explain the concept of an open-ended approach based on TPACK, the concept of mathematical reasoning and the relationship between an open-ended approach based on TPACK and mathematical reasoning. The result of this study are: (1) TPACK-based Open ended Approach is learning that presents a problem that has more than one correct method or solution, which is presented with the help of ICT-based media. (2) Mathematical reasoning is the ability to conclude and prove a statement, and solve problems in mathematics. (3) TPACK-based open ended approach can improve mathematical reasoning.